Pendekatan Kepemimpinan Kepala Sekolah dalam Peningkatan Kinerja dan Produktivitas Guru di SMP Swasta Samarinda - Monica, Metta Virya; Setiyati, Setiyati; Tarman, Tarman; Warman, Warman (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to examine the role of school principals in increasing teacher work productivity in junior high schools in Samarinda City. This research uses a qualitative approach with a case study method. Data collection was carried out through semi-structured interviews with school principals, deputy principals and teachers as informants, as well as observation and documentation. The research results show that the planning carried out by the school principal has run optimally. The school principal prepares plans systematically, provides assistance to teachers to improve the quality of teaching. This planning includes preparing training and workshop schedules for teachers, providing facilities, and providing motivation. Follow-up to this plan includes recording deficiencies during class observations, calling individual teachers, and discussing the results through teacher council meetings. Good planning by school principals accelerates improvements in teacher performance, which has a positive impact on schools and students to achieve optimal results. This emphasizes the important role of school principals in designing strategies to increase teacher work productivity and manage schools effectively.